Electrochemical conversion of CO2 to carbon and oxygen in LiCl–Li2O melts. (1st February 2016) - Li, Liangxing; Shi, Zhongning; Gao, Bingliang; Hu, Xianwei; Wang, Zhaowen
Highlights: CO2 can be significantly absorbed by LiCl–Li2 O. Carbon is obtained by the electrochemical reduction of carbonate ions. Oxygen is evolved from the anode. The anodic CO2 /O2 ratio increases with increasing anodic current density. Abstract: Carbon dioxide was electrochemically decomposed to carbon and oxygen gas in molten LiCl–5.0 wt.% Li2 O molten salts at 903 K using a titanium cathode and inert platinum anode. CO2 chemically dissolves into the LiCl–Li2 O melt by reacting with Li2 O, changing the electrolyte LiCl–Li2 O–CO2 into Li2 CO3 and LiCl. Carbonate anions are electrochemically reduced to carbon on the cathode, while oxygen complexes of carbonate anions are oxidized at the anode, generating O2 . Electrolysis of the LiCl–5.0 wt.% Li2 O molten salt under a CO2 atmosphere at 0.05 A/cm 2 yields anodic gas with a CO2 /O2 ratio of 0.42. The CO2 /O2 ratio increases with increasing current density. The proposed concept may provide oxygen and fuel supplies to future explorers and inhabitants of Mars.